2007
DOI: 10.2167/irgee213.0
|View full text |Cite
|
Sign up to set email alerts
|

The Environmental Knowledge and Attitudes of Prospective Teachers in Lebanon: A Comparative Study

Abstract: This paper presents data arising from a study of final-year primary and secondary teaching students in Lebanon using an equivalent Australian sample as a comparative reference group. It was found that the Lebanese students lagged behind their Australian counterparts with respect to their knowledge of global environmental issues, and displayed a narrower awareness of national environmental issues. Despite higher scores on the environmental attitudes scale that was administered, they were more likely to be scept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 20 publications
1
17
0
2
Order By: Relevance
“…The results of that study revealed that the forest category is not included in Athens and included in Sparta by only 4%. Similarly, Vlaardingerbroek & Taylor (2007) listed the loss of forests, air pollution, and the pollution of beaches among the biggest environmental problems in Lebanon.…”
Section: Findings Regarding Eshmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of that study revealed that the forest category is not included in Athens and included in Sparta by only 4%. Similarly, Vlaardingerbroek & Taylor (2007) listed the loss of forests, air pollution, and the pollution of beaches among the biggest environmental problems in Lebanon.…”
Section: Findings Regarding Eshmentioning
confidence: 99%
“…Based on the assumption that there is a relationship among knowledge, attitude, and behavior (Bradley, Waliczek & Zajicek, 1999;Gayford, 1998), there is a need for environmental education (McMillan, 2003) to positively influence society's attitude, awareness, and interest toward the environment and to equip individuals with eco-friendly behaviors (Bogner, 1998;Grodziéska-Jurczak, Stepska, Nieszporek & Bryda, 2006;Zelezny, 1999). This is because there exists a direct relationship between environmental education and the attitudes and behaviors toward the environment (Vlaardingerbroek & Taylor, 2007). Environmental education has a strong history in shaping studies of nature, experiences with nature, and environmental science studies (Kyburz-Graber, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…For instance in schools, students who have high scientific knowledge tend to choose more appropriate decisions (Ugulu, Sahin, & Baslar, 2013). This means there is a direct relationship between environmental education and environmentally responsible attitudes and behaviors (Vlaardingerbroek and Taylor 2007).…”
Section: Environmental Attitude Environmental Behavior and Environmementioning
confidence: 99%
“…Aynı zamanda katılımcıların çevre ve çevre sorunlarına ilişkin algılarına yönelik araştırmalar da mevcuttur (Ateş ve Karatepe, 2013;Aydın, 2011;Seçgin, Yalvaç ve Çetin, 2010). Çevre eğitimi, çevreye yönelik olumlu tutumlar, çevreye karşı sorumlu davranışlar ve çevre bilinci konu/kavramları da araştırmacıların çalışma alanlarındandır (Demir ve Yoldaş, 2016;Eagles ve Demare, 1999;Erol ve Gezer, 2006;Esa, 2010;Pooley ve O'Connor, 2000;Sungur, 2017;Şama, 2003;Taylor, Doff, Jenkins ve Kennelly, 2007;Tuncer, Sungur, Tekkaya ve Ertepınar, 2007;Vlaardingbroek ve Taylor, 2007). Yukarıda bahsedilen araştırmalarda da incelenen bu çevresel tutum ve davranışları etkileyen unsurlardan biri de çevre etiğidir (Gerçek, 2016).…”
Section: Introductionunclassified